2017
DOI: 10.1111/cid.12548
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and histologic characterization of alveolar bone from hypertensive patients

Abstract: These observations suggest that hypertensive patients treated with renin-angiotensin system antagonists have regular alveolar bone with respect to bone structure and histological parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Support for this hypothesis comes from studies showing that hypertension is linked to osteoporosis, and antihypertensive drugs reduce the fracture risk, respectively (Cappuccio et al, 2000;Vestergaard et al, 2009). The clinical relevance of the present study is maybe twofold: first, losartan prevents systemic bone loss in hypertensive patients, thereby also supporting the quality of the alveolar bone before implants are placed (Bastos et al, 2010;Fabris et al, 2017). Secondly, losartan supports bone remodeling after implants were placed causing a better biomechanical stability in the long term.…”
Section: Discussionsupporting
confidence: 55%
“…Support for this hypothesis comes from studies showing that hypertension is linked to osteoporosis, and antihypertensive drugs reduce the fracture risk, respectively (Cappuccio et al, 2000;Vestergaard et al, 2009). The clinical relevance of the present study is maybe twofold: first, losartan prevents systemic bone loss in hypertensive patients, thereby also supporting the quality of the alveolar bone before implants are placed (Bastos et al, 2010;Fabris et al, 2017). Secondly, losartan supports bone remodeling after implants were placed causing a better biomechanical stability in the long term.…”
Section: Discussionsupporting
confidence: 55%
“…A retrospective cohort study included 1499 implants in 728 patients demonstrated that the patients using anti-hypertensive drugs lost only 2 implants (Table 2) [7]. Other study revealed that the histological appearance of bone derived from hypertensive patients was normal [9].…”
Section: Resultsmentioning
confidence: 99%
“…24 In general, antihypertensive prescriptions help in bone generation and a lesser risk of bone fractures. 25 According to a study by Seki et al, antihypertensive medicines adversely affect dental implants. Deeper peri-implant pockets and more bone resorption were seen, which may indicate a deleterious effect on bone metabolism.…”
Section: /455mentioning
confidence: 99%